2023
DOI: 10.2147/dddt.s391503
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Mechanism of Schisandrol A and Its Metabolites on Pulmonary Fibrosis Based on Plasma Metabonomics and Network Analysis

Abstract: Background: Schisandrol A (Sch A) is the main active ingredient of Schisandra chinensis (Turcz.) Baill. Our previous study showed that Sch A has anti-pulmonary fibrosis (PF) activity, but its metabolic-related mechanisms of action are not clear. Methods: Here, we explored the therapeutic mechanisms of Sch A on PF by ultra-high performance liquid chromatography coupled with tandem mass spectrometry (UPLC-MS/MS) metabolomics approach and network analysis. The metabolites of Sch A in mice (bleomycin + Sch A high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The ultra-high performance liquid chromatography coupled with tandem mass spectrometry metabolomics was used to explore the therapeutic mechanisms of schisandrol A against pulmonary fibrosis and revealed that TGF-β1-VIM-carnosine and TGF-β1-ID3creatine pathway were key pathways of Sch A modulating the metabolic disorders [137]. Serum metabolomics combined with UPLC/MS analyzed the effective substances and action mechanisms of Ziziphi Spinosae Semen extract for insomnia treatment [138].…”
Section: Efficacy Evaluation Of Herbal Medicine and Natural Productsmentioning
confidence: 99%
“…The ultra-high performance liquid chromatography coupled with tandem mass spectrometry metabolomics was used to explore the therapeutic mechanisms of schisandrol A against pulmonary fibrosis and revealed that TGF-β1-VIM-carnosine and TGF-β1-ID3creatine pathway were key pathways of Sch A modulating the metabolic disorders [137]. Serum metabolomics combined with UPLC/MS analyzed the effective substances and action mechanisms of Ziziphi Spinosae Semen extract for insomnia treatment [138].…”
Section: Efficacy Evaluation Of Herbal Medicine and Natural Productsmentioning
confidence: 99%
“…Idiopathic pulmonary fibrosis (IPF) affects the lung parenchyma and is characterized by a decline in lung functions, abnormal deposition of extracellular matrix, and interstitial fibrosis that worsens with time. 1 , 2 The incidence of PF has been rising year after year in recent years; 3 however, IPF’s onset and progression have complex mechanisms that are still unknown. 4–6 In addition to the recognized risk factors for IPF, such as smoke, environmental elements, comorbidities, and viral infections, various other processes are associated with the disease.…”
Section: Introductionmentioning
confidence: 99%